Connection between electrical conductivity and diffusion coefficient of a conductive porous material filled with electrolyte. (December 2017) - Sevostianov, I.; Trofimov, A.; Merodio, J.; Penta, R.; Rodriguez-Ramos, R.
Abstract: The paper focuses on the cross-property connection between the effective electrical conductivity and the overall mass transfer coefficient of a two phase material. The two properties are expressed in terms of the tortuosity parameter which generalized to the case of a material with two conductive phases. Elimination of this parameter yields the cross-property connection. The theoretical derivation is verified by comparison with computer simulation.